Biological Significance of Marine Actinobacteria of East Coast of Andhra Pradesh, India - Kavitha, Alapati; Savithri, Handanahal S. (Frontiers in Microbiology, 2017)
An attempt was made to identify actinobacterial strains present in the marine soil of East Coast regions viz., Chirala, Bapatla and Peddaganjam, Andhra Pradesh; Kanyakumari, Tamil Nadu and Goa, Goa along with the study of their antimicrobial potential. Eight out of seventy three actinobacterial strains isolated from these regions showed strong antimicrobial activity against Gram positive bacteria, Gram negative bacteria and Candida albicans. Molecular identification (16S rRNA analysis) of the eight strains revealed that they belong to Dietzia sp., Kocuria sp., Nocardiopsis sp. and Streptomyces spp. ISP (International Streptomyces project) -1, ISP-2 and starch casein media supported high antimicrobial potential after 5 to 6 days of growth. Production of antimicrobials by the strains varied significantly with different carbon and nitrogen sources. Gas chromatography mass spectrometry (GCMS) analysis of volatile compounds produced by the strains illustrated an array of antimicrobial compounds such as 1, 2-benzene dicarboxylic acid, 2-piperidinone, pyrrolo[1,2-a]pyrazine-1,4-dion, phenyl ethyl alcohol, 3-phenyl propionic acid etc. Ours is the first report on the study and detection of above mentioned antimicrobial metabolites from Dietzia sp. (A3), Kocuria sp. (A5) and Nocardiopsis sp. (A7). By sequence based analysis for secondary metabolites, non-ribosomal peptide synthetase (NRPS) gene cluster was noticed in six strains (A2, A3, A4, A6, A7 and A8) and none of them had polyketide synthase (PKS) system. The present study intimates the biological potentiality of the actinobacterial strains isolated from East Coast of Andhra Pradesh, India which reveals further scope to investigate new bioactive compounds by employing both natural product chemistry and modern biotechnological aspects.